Maataloustuotannon ennakointi - Kettunen, Lauri (Agricultural and Food Science, 1974)
Short term forecasts of agricultural production are used primarily in everyday agricultural policy, for example in the predictions of production and consuption of pork and beef, which indicate the need of exports and/or imports in order to achieve the target prices of these products. In some cases short term forecasts might also be used for setting targets. For example the market outlook could be taken into account when the target prices are determined so that they could be easily achieved. Long term predictions, covering 5 10 years, are useful above all in the planning of agricultural policy. The changes in the structure of agriculture and the agricultural population are responsible for the main part (up to 2/3) of the changes in the agricultural production in some countries. Together with an increase in the farm size, the use of the new technology becomes more general and specialization increases, which leads to larger variations in production. Forecasting these factors is clearly important for successful long term planning in agricultural policy. The accuracy of predictions is not always good even in short term forecasts despite the highly developed mathematical models. In the long run it is pointless to make detailed forecasts for different products, since by changing the price ratios it is possible to regulate production. Instead, more resources should be assigned to the forecasting of the technical-biological development, i.e. to the forecasting of the growth of the yields in crop and animal production and the effects of the changes in the structure of agriculture.